2000
DOI: 10.1042/0264-6021:3490091
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids induce a near-total suppression of hyaluronan synthase mRNA in dermal fibroblasts and in osteoblasts: a molecular mechanism contributing to organ atrophy

Abstract: Glucocorticoid (GC) administration induces atrophy of skin, bone, and other organs, partly by reducing tissue content of glycosaminoglycans, particularly hyaluronic acid (HA). We took advantage of the recent cloning of the three human hyaluronan synthase (HAS) enzymes (HAS1, HAS2 and HAS3), to explore the molecular mechanisms of this side effect. Northern and slot blots performed on RNA extracted from cultured dermal fibroblasts and the MG-63 osteoblast-like osteosarcoma cell line indicated that HAS2 is the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
49
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 50 publications
3
49
0
2
Order By: Relevance
“…The most conspicuous HAS inhibitors reported to date include hydrocortisone (24), which suppresses HAS2 expression in mesothelial cells almost entirely, and dexamethasone, another glucocorticoid that rapidly down-regulates HAS2 expression in skin fibroblasts (30). The former study again reported no effect on HAS1 or HAS3 message levels, suggesting that HAS2 may be the most transiently regulated of the three genes.…”
Section: Discussionmentioning
confidence: 58%
“…The most conspicuous HAS inhibitors reported to date include hydrocortisone (24), which suppresses HAS2 expression in mesothelial cells almost entirely, and dexamethasone, another glucocorticoid that rapidly down-regulates HAS2 expression in skin fibroblasts (30). The former study again reported no effect on HAS1 or HAS3 message levels, suggesting that HAS2 may be the most transiently regulated of the three genes.…”
Section: Discussionmentioning
confidence: 58%
“…HAS3 transcript levels are increased in response to IFN-␥ and decreased with TGF-␤ in cultured keratinocytes, whereas HAS1 and 2 levels were unchanged (49). In human dermal fibroblasts, basal transcript levels of HAS2 were significantly suppressed with the administration of glucocorticoids, therapeutic agents with pronounced side effects such as organ atrophy (62). When measuring HAS transcript levels in human fibroblast-like synoviocytes, TGF-␤ potently activated HAS1 but suppressed HAS3 in a dose-dependent manner (52).…”
Section: Discussionmentioning
confidence: 88%
“…Over the years, much work has focused on the interaction of hyaluronan with various extracellular matrix molecules such as aggrecan and versican (23). These interactions have proven critical for tissue volume changes and the creation and stability of cell-free spaces (36,41,42,55,59,62). Another area of interest is its interaction with a number of cell surface receptors, most notably CD44 (18).…”
mentioning
confidence: 99%
“…The regulation of HAS genes in vivo by physiological factors such as nutrition has not previously been studied, and the present study is thus theˆrst attempt of this sort. It has been shown that human skinˆbroblasts abundantly expressed HAS1 and HAS2 mRNA, 12,27) whereas epidermal keratinocytes had a high HAS3 mRNA content. 13) Among them, the activity of HAS2 and HAS3 is thought to be important, but we found their mRNA levels to be very low.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three members (HAS1, HAS2 and HAS3), HAS2 functions as the major producer of hyaluronan in the dermis, 11) whereas HAS3 is the one in the epidermis. 12,13) Studies using keratinocytes and dermalˆbroblasts have shown that these enzymes are regulated by some cytokines and glucocorticoids. However, their regulation in vivo has not yet been studied well.…”
mentioning
confidence: 99%